Unlocking the Economic Potential of Cultural Heritage: Women’s Empowerment in the Creative Economy of Developing Countries - ., Surti; Pratomo, Devanto Shasta; Santoso, Dwi Budi; Pangestuty, Farah Wulandari (Journal of Ecohumanism, 2024)
This literature review explores how empowering women in a culture-based creative economy can preserve cultural heritage while encouraging economic competitiveness in developing countries. Through a systematic analysis of 44 studies, key findings emerged. First, cultural heritage offers economic opportunities through sustainable tourism and creative entrepreneurship. Second, women face challenges such as marginalization, limited resources, and socio-cultural obstacles in conservation efforts. Third, integrating traditional wisdom into creative products, entrepreneurship training, and marketing can empower women economically. Fourth, government policy, financial support, use of digital technology, and multi-stakeholder involvement are important factors. Fifth, best practices from various countries demonstrate successful replication models. The review concludes that empowering women to preserve cultural heritage opens up sustainable economic development by leveraging local strengths, thus requiring synergistic efforts from the government, stakeholders, and women. Preserving cultural heritage through empowering women is a dual opportunity for developing countries to maintain their identity while driving economic progress.